Nonclassic fibrodysplasia ossificans progressiva: A child from Angola with an ACVR1G328E variant. Issue 8 (11th May 2021) - Martín‐García, Diana; Towler, O. Will; Xu, Meiqi; Alfonso‐Hernández, Osmany; Oliveira, Paula R.; Alonso‐Clavo, Marleny; Shore, Eileen M.; Kaplan, Frederick S.
Abstract: Little is known about FOP in Africa and few cases of nonclassic fibrodysplasia ossificans progressiva (FOP) have been reported on the continent. Here we report a three‐year‐old girl from Angola with a nonclassic FOP clinical presentation that is characterized by complex malformations of the toes and fingers, reduction defects of the digits, absence of nails, progressive heterotopic ossification, and a confirmed heterozygous ACVR1 variant at c.983G > A. Emerging knowledge of FOP can serve as a catalyst for increasing awareness of FOP in under‐represented medical communities by achieving a correct FOP diagnosis, improving access of individuals with FOP to clinical trial recruitment, and enhancing the ability of affected individuals to be part of and interact with the international FOP community.